Method for synthesizing imine based on SiC catalysis and SiC catalyst
By preparing porous SiC catalysts for the oxidative coupling reaction of benzylamine, the problems of high cost and difficult catalyst recovery in existing imine synthesis methods are solved, and efficient and low-cost imine synthesis is achieved.
Patent Information
- Application Number
- CN202411215491.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
AI Technical Summary
Existing methods for synthesizing imines are costly and complex, traditional metal catalysts are difficult to recycle and reuse, and non-metal catalysts have insufficient catalytic activity, making it difficult to meet the requirements of green development.
A porous SiC catalyst was prepared by hydrothermal etching, calcination and acid-base treatment, and used for the oxidative coupling reaction of benzylamine. The catalyst is easy to recycle.
The prepared porous SiC catalyst has a high specific surface area and pore structure, good catalytic stability, high reaction conversion and selectivity, and low cost, making it suitable for industrial applications.
Smart Images

Figure CN119327493A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a method for synthesizing imines based on SiC catalysis and a SiC catalyst. Background Art
[0002] As an important organic compound, imines are widely used in industry, agriculture, biomedicine and other fields. However, traditional imine synthesis methods, such as hydrogenation coupling reaction of nitro compounds and oxidative condensation reaction of amines and alcohols, have the problems of high cost and complex preparation process, which limits the further development and application of imines. In order to solve these problems, scientists have been exploring more efficient and lower-cost imine synthesis methods.
[0003] The oxidative coupling reaction of benzylamine is an effective method for preparing imines, which has high atom economy and is environmentally friendly. Through this reaction, important intermediate imines and their derivatives for pharmaceuticals, dyes and fine chemicals can be synthesized. In some cases, this reaction can be carried out under milder conditions with high conversion rate and selectivity. However, the current benzylamine oxidation process usually requires the use of metal organic complexes that are difficult to separate and recycle as catalysts, and most of them use precious metal catalysts such as rhodium, ruthenium, iridium and palladium. Although these metal catalytic materials have high catalytic activity, their production cost is high and does not meet the requirements of green and sustainable development. In recent years, researchers have begun to focus on non-metallic catalysts, such as carbon materials, C3N4, etc. Although they are cheap and easy to obtain and show certain catalytic activity, the catalysts are difficult to recycle after use, which increases the cost and reduces the practicality of the catalyst.
[0004] SiC is a non-oxide semiconductor material with good thermal and electrical conductivity, high temperature resistance and acid-base corrosion resistance, and is a catalytic material with broad application prospects. SiC's unique physical and chemical properties make it exhibit good cycle stability, and it can be directly recycled and reused after the reaction is completed, with low cost throughout the entire life cycle. Therefore, it is of great significance to develop an efficient SiC-based non-metallic catalyst for the oxidative coupling reaction of benzylamine. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for synthesizing imines based on SiC catalysis.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:
[0009] The SiC is uniformly dispersed in the etching solution, and a hydrothermal reaction is carried out. After the reaction is completed, the SiC is cooled to room temperature, and deionized water is added and repeatedly centrifuged and washed until it is neutral; the obtained solid powder is mixed with deionized water and ultrasonicated, and the supernatant is removed by centrifugation. The reaction is repeated many times until the supernatant is colorless and transparent, and the solid powder at the bottom is dried to obtain a coarse porous SiC containing carbon impurities;
[0010] The crude porous SiC is calcined in an air atmosphere to remove impurity carbon; the calcined porous SiC is immersed in an acid or alkaline solution to remove the silicon dioxide on the surface, and finally washed with deionized water and ethanol, and dried to obtain a SiC catalyst;
[0011] The SiC catalyst and benzylamine are dissolved in a solvent to carry out an oxidative coupling reaction. After the reaction is completed, the SiC catalyst and the supernatant are separated to obtain imine.
[0012] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis of the present invention, the etching solution is a mixed acid solution of HF and HNO3.
[0013] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis of the present invention, the volume ratio of HF to HNO3 is 0.5-5:1.
[0014] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis of the present invention, the hydrothermal reaction has a reaction temperature of 80 to 140° C. and a reaction time of 3 to 10 hours.
[0015] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis according to the present invention, the calcination comprises the following steps: the calcination temperature is 500 to 950°C, the calcination time is 1 to 6 hours, and the heating rate is 8 to 15°C / min.
[0016] As a preferred embodiment of the method for synthesizing imines based on SiC catalysis according to the present invention, the acidic solution is HF, and the alkaline solution is KOH or NaOH with a concentration of 0.5 to 6.0 mol / L.
[0017] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis of the present invention, the drying temperature is 50-70°C.
[0018] As a preferred embodiment of the method for synthesizing imines based on SiC catalysis according to the present invention, the specific surface area of the SiC catalyst is 25 to 180 m2 / g.
[0019] As a preferred embodiment of the method for synthesizing imines based on SiC catalysis of the present invention, the addition amount of the SiC catalyst is 8% to 20% of the mass of benzylamine; and the reaction solvent includes one of acetonitrile, ethanol and methanol.
[0020] As a preferred embodiment of the method for synthesizing imine based on SiC catalysis of the present invention, the oxidative coupling reaction has a reaction temperature of 30 to 80° C. and a reaction time of 0.5 to 3 h.
[0021] Beneficial effects of the present invention:
[0022] The porous SiC material prepared by the present invention is a metal-free catalyst, which greatly reduces the cost of the catalyst. The catalyst has a large specific surface area, pore volume and rich pore structure, which is very helpful for catalyzing the oxidative coupling of benzylamine to prepare imine. In addition, the high temperature resistance and acid and alkali corrosion resistance of SiC make it show excellent catalytic stability, and it is very easy to recycle after the reaction is completed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0024] Figure 1 This is a transmission electron microscope image of the porous SiC catalyst provided in Example 1 of the present invention.
[0025] Figure 2 This is a transmission electron microscopy image of the uncorroded SiC catalyst provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0030] The performance of the material prepared in the embodiment of the present invention was tested as follows:
[0031] The conversion rate and imine selectivity of the benzylamine oxidation reaction catalyzed by the catalyst are obtained by gas chromatography analysis.
[0032] Example 1
[0033] This embodiment provides a method for synthesizing imine based on SiC catalysis, specifically:
[0034] 3 g of SiC was weighed and uniformly dispersed in 30 mL of a mixed acid solution of HF and HNO3 (volume ratio of 1:1), and then transferred to a hydrothermal reactor for hydrothermal reaction at 100 ° C for 4 hours for etching. After the reaction, it was cooled to room temperature, deionized water was added and repeated centrifugation washing was performed until the solution was neutral; the solid powder at the bottom of the centrifuge tube was taken into a beaker, deionized water was added and ultrasonicated for 30 minutes, and the supernatant was removed by centrifugation. This process was repeated many times until the supernatant was colorless and transparent, and then the solid powder at the bottom was placed in an oven at 60 ° C for drying and grinding to obtain porous SiC containing carbon impurities.
[0035] Subsequently, the dried sample was evenly spread on a high-temperature resistant porcelain boat and placed in a muffle furnace. The temperature was raised to 700°C at 10°C / min and calcined for 3 hours to remove impure carbon. The calcined porous SiC was immersed in an HF solution for 10 hours to remove silica, and finally washed with deionized water and ethanol, and dried in a constant temperature oven at 65°C to obtain a pure porous SiC catalyst.
[0036] A porous SiC catalyst, 1 mmol of benzylamine and 10 ml of acetonitrile were added into a stainless steel reactor (the amount of the catalyst was 13% of the mass of the benzylamine), heated to 50° C., and reacted for 3 hours in an air atmosphere to obtain an imine.
[0037] Figure 1 This is a transmission electron microscope image of the porous SiC catalyst prepared in Example 1 of the present invention. It can be seen from the image that the catalyst contains a very rich pore structure, indicating that more reaction sites are exposed on the surface, which can catalyze the oxidation of benzylamine.
[0038] The porous SiC material prepared in this embodiment has no change in reaction performance after 10 uses. As for the porous carbon material, due to the oxidation reaction, the carbon material is inevitably oxidized into CO and CO2. SiC is an inorganic material with very good chemical stability.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that the reaction time of the hydrothermal reaction is adjusted to 3 hours, and the rest of the preparation process is the same as that of embodiment 1, and the SiC catalyst is prepared and catalyzes the synthesis of imine.
[0041] Example 3
[0042] The difference between this embodiment and embodiment 1 is that the reaction time of the hydrothermal reaction is adjusted to 10 hours, and the rest of the preparation process is the same as that of embodiment 1, and the SiC catalyst is prepared and catalytically synthesizes imine.
[0043] Comparative Example 1
[0044] The difference between this embodiment and embodiment 1 is that no hydrothermal reaction is performed, that is, SiC is not etched, and the rest of the preparation process is the same as that of embodiment 1, and SiC catalyst is prepared and catalyzes the synthesis of imine.
[0045] Figure 2 This is a transmission electron microscope image of the SiC-based metal-free catalyst prepared in Comparative Example 1 of the present invention.
[0046] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0047] Table 1
[0048] <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) Conversion rate (%) Imine selectivity (%) Example 1 165 27 98.6 99 Example 2 136 25 72.3 99 Example 3 125 20 70 99 Comparative Example 1 27 10 13.2 99
[0049] It can be seen from the above table that adjusting the etching time has a significant effect on the material properties. This is because the longer the etching time, the more SiO2 is corroded, thereby producing more pore structures and exposing more reaction sites. According to the results in the above table, the best technical effect can be obtained when the etching time in the present invention is 4h.
[0050] Example 4
[0051] The difference between this embodiment and embodiment 1 is that the temperature of the hydrothermal reaction is adjusted to 140° C., and the rest of the preparation process is the same as that of embodiment 1, and a SiC catalyst is prepared and catalyzes the synthesis of imine.
[0052] Example 5
[0053] The difference between this embodiment and embodiment 1 is that the temperature of the hydrothermal reaction is adjusted to 80° C., and the rest of the preparation process is the same as that of embodiment 1, and a SiC catalyst is prepared and catalyzes the synthesis of imine.
[0054] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.
[0055] Table 2
[0056] <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) Conversion rate (%) Imine selectivity (%) Example 1 165 27 98.6 99 Example 4 151 32 89.1 99 Example 5 92 18 72.6 99
[0057] It can be seen from the above table that adjusting the temperature of the hydrothermal reaction has a significant effect on the material properties. This is because the hydrothermal reaction etches SiC, and the temperature of the hydrothermal reaction affects the rate of corrosion of SiO2. The higher the temperature, the faster the reaction, but it is prone to excessive corrosion, resulting in an increase in pore size and a decrease in specific surface area. When the temperature is too low, the reaction rate is slow, resulting in fewer exposed reaction sites. According to the results in the above table, the best technical effect can be obtained when the temperature of the hydrothermal reaction in the present invention is 100°C.
[0058] Example 6
[0059] The difference between this embodiment and embodiment 1 is that the calcination time is adjusted to 1 hour, and the rest of the preparation process is the same as that of embodiment 1, and the SiC catalyst is prepared and catalyzes the synthesis of imine.
[0060] Example 7
[0061] The difference between this embodiment and embodiment 1 is that the calcination time is adjusted to 2 hours, and the rest of the preparation process is the same as that of embodiment 1, and the SiC catalyst is prepared and catalyzes the synthesis of imine.
[0062] Example 8
[0063] The difference between this embodiment and embodiment 1 is that the calcination time is adjusted to 6 hours, and the rest of the preparation process is the same as that of embodiment 1, and the SiC catalyst is prepared and catalyzes the synthesis of imine.
[0064] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.
[0065] Table 3
[0066] <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) Conversion rate (%) Imine selectivity (%) Example 1 165 27 98.6 99 Example 6 189 14 48.3 99 Example 7 172 16 65.6 99 Example 8 169 15 50 99
[0067] It can be seen from the above table that adjusting the calcination time has a significant effect on the material properties. This is because the carbon released during the etching process is not completely reacted during the calcination process, and the active sites in the pores of the porous silicon carbide cannot be fully exposed. According to the results in the above table, the best technical effect can be obtained when the calcination time is 4 hours in the present invention.
[0068] Example 9
[0069] The difference between this embodiment and embodiment 1 is that the volume ratio of the mixed acid solution of HF and HNO3 is adjusted to 0.5:1, and the rest of the preparation process is the same as that of embodiment 1 to prepare SiC catalyst and catalyze the synthesis of imine.
[0070] Example 10
[0071] The difference between this embodiment and embodiment 1 is that the volume ratio of the mixed acid solution of HF and HNO3 is adjusted to 2:1, and the rest of the preparation process is the same as that of embodiment 1 to prepare SiC catalyst and catalyze the synthesis of imine.
[0072] Embodiment 11
[0073] The difference between this embodiment and embodiment 1 is that the volume ratio of the mixed acid solution of HF and HNO3 is adjusted to 5:1, and the rest of the preparation process is the same as that of embodiment 1 to prepare SiC catalyst and catalyze the synthesis of imine.
[0074] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.
[0075] Table 4
[0076] <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) Conversion rate (%) Imine selectivity (%) Example 1 165 27 98.6 99 Example 9 57 15 34 99 Example 10 49 13 41 99 Embodiment 11 50 12 39 99
[0077] It can be seen from the above table that adjusting the volume ratio of the mixed acid solution of HF and HNO3 has a significant effect on the material properties. This is because the original silicon carbide particles are large, and the oxidation reaction involving HNO3 is carried out from the outside to the inside. When the HF content is low, the Si-O reaction is incomplete, and the internal Si-C bond is hindered by the external surface Si-O, making it difficult to fully react with HNO3. The Si-O bond content has not yet reached a high concentration, resulting in the entire reaction not reaching an ideal state and insufficient corrosion. According to the results in the above table, the best technical effect can be obtained when the volume ratio of the mixed acid solution of HF and HNO3 in the present invention is 3:1.
[0078] Example 12
[0079] The difference between this embodiment and embodiment 1 is that the etching solution is adjusted to HNO3 and KOH, SiC is first oxidized by HNO3 and then corroded by KOH, and the rest of the preparation process is the same as that of embodiment 1 to obtain SiC catalyst and catalyze the synthesis of imine.
[0080] Example 13
[0081] The difference between this embodiment and embodiment 1 is that the etching solution is adjusted to HNO3 and NaOH, SiC is first oxidized by HNO3 and then corroded by NaOH, and the rest of the preparation process is the same as that of embodiment 1 to obtain SiC catalyst and catalyze the synthesis of imine.
[0082] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 5.
[0083] Table 5
[0084] <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) Conversion rate (%) Imine selectivity (%) Example 1 165 27 98.6 99 Example 12 82 13 42.7 99 Example 13 73 12 29.6 99
[0085] It can be seen from the above table that the adjustment of the etching solution has a significant effect on the material properties. This is because the acid and alkali will neutralize and need to react step by step, and the in-situ oxidized SiO2 cannot react in time, resulting in an incomplete reaction. According to the results in the above table, the best technical effect can be obtained when the etching solution in the present invention is HF and HNO3.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 1 is that SiC is adjusted to biomass waste tea fruit peel, and the rest of the preparation process is the same as Example 1 to obtain a porous biomass carbon material.
[0088] The specific surface area of tea peel-based porous biomass carbon material is 1600m 2 / g, with an average pore size of 2.61nm. The performance test was carried out by adding the catalyst, 1mmol benzylamine and 10ml acetonitrile into a microreactor, heating the reactor to 70℃ for 2h to obtain imine; wherein, the amount of catalyst was 28% of the mass of benzylamine, and the conversion rate of the oxidation reaction of benzylamine catalyzed by tea peel-based porous biomass carbon material was 99.1% and the selectivity was 99% by gas chromatography. After 5 uses, the conversion rate was reduced from 90.5% to 84.6%.
[0089] It can be seen that the present invention can synthesize a porous silicon carbide material with a large specific surface area, pore volume and rich pore structure by a simple method, and can be used as a metal-free catalyst to catalyze the benzylamine oxidation reaction, with the advantages of short reaction time, high conversion rate and selectivity. Compared with other metal-free catalysts, it exhibits excellent catalytic stability and is extremely easy to recycle after the reaction.
[0090] In chemical reactions, defect sites on the catalyst surface are usually active sites for the reaction. The present invention can expose many edges and corners of complete crystals, i.e. defect sites, through chemical etching, while increasing the specific surface area of SiC, which is more conducive to the adsorption and activation of reactants.
[0091] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for synthesizing imines based on SiC catalysis, characterized in that: include, The SiC is uniformly dispersed in the etching solution, and a hydrothermal reaction is carried out. After the reaction is completed, the SiC is cooled and washed to neutrality to obtain a solid powder. The solid powder is mixed with deionized water and ultrasonicated, and the supernatant is removed by centrifugation. The process is repeated many times until the supernatant is colorless and transparent, and the solid powder at the bottom is dried to obtain a coarse porous SiC containing carbon impurities. The crude porous SiC is calcined in an air atmosphere to remove impurity carbon; the calcined porous SiC is immersed in an acid or alkaline solution to remove the silicon dioxide on the surface, and finally washed and dried to obtain a SiC catalyst; The SiC catalyst and benzylamine are dissolved in a solvent to carry out an oxidative coupling reaction. After the reaction is completed, the SiC catalyst and the supernatant are separated to obtain imine.
2. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The etching solution is a mixed acid solution of HF and HNO3.
3. The method for synthesizing imines based on SiC catalysis according to claim 2, characterized in that: The volume ratio of HF to HNO3 is 0.5-5:
1.
4. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The hydrothermal reaction has a reaction temperature of 80 to 140° C. and a reaction time of 3 to 10 hours.
5. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The calcination process comprises a calcination temperature of 500 to 950° C., a calcination time of 1 to 6 hours, and a heating rate of 8 to 15° C. / min.
6. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The acidic solution is HF, and the alkaline solution is KOH or NaOH with a concentration of 0.5 to 6.0 mol / L.
7. The method for preparing a porous SiC material according to claim 1, characterized in that: The drying temperature is 50-70°C.
8. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The specific surface area of the SiC catalyst is 25 to 180 m 2 / g.
9. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The added amount of the SiC catalyst is 8% to 20% of the mass of benzylamine; and the reaction solvent comprises one of acetonitrile, ethanol and methanol.
10. The method for synthesizing imines based on SiC catalysis according to claim 1, characterized in that: The oxidative coupling reaction has a reaction temperature of 30 to 80° C. and a reaction time of 0.5 to 3 h.